A Robust Speed Controller Design for PMSM Using PIλDμ Controllers - Ersoy, Hakan; Akgul, Berke; Akpinar, Emin; Kartci, Aslihan; Ayten, Umut Engin (IEEE, 2024)
This study proposes the design of Fractional-Order Proportional-Integral-Derivative ((PID mu)-D-lambda) controllers for Permanent Magnet Synchronous Motors (PMSMs). PMSMs are essential in high-precision industrial applications due to their high efficiency and outstanding speed regulation. (PID mu)-D-lambda controllers, unlike conventional PID controllers, use fractional calculus to provide an extra degree of flexibility, allowing the system to change and diversify over a wide range of operating states. By performing a series of simulations, we analyze the performance metrics of controllers and compare it with integer-order PID controllers. Our main focus is on the evaluation of speed control response time, overshoot, and steady state error. The results show that the (PID mu)-D-lambda controller effectively improves the dynamic and static performance of PMSM without loss of stability. As a result, the design methodology from simulations and comparative statistics confirm that (PID mu)-D-lambda controllers have the potential to be superior in maintaining precise control over integer-order PIDs in complex electromechanical systems.
Keywords: Digital Signal Processing; Fractional-Order PID; Permanent Magnet Synchronous Motors; PID; PMSM; MAGNET SYNCHRONOUS MOTOR; OPTIMIZATION; Engineering; Telecommunications